The Effectiveness of Educational Video Learning on Patient Safety Knowledge in Clinical Clerkship Student in Teaching Hospital - Santi Anugrahsari; Hafid Abbas; Suryadi Suryadi (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Patient safety is the main point to consider and promote in every health service at various levels of health facilities. It is highly prominent for students, especially clinical clerkships, as future doctors. Currently, the use of educational video is a popular learning medium for students. Yet, no research reveals how clinical clerkships are exposed to patient safety after learning through videos before taking education at teaching hospitals. The current study aimed to describe the learning outcomes of patient safety education videos in clinical clerkships. It employed a descriptive-analytic method. Twenty-three clinical clerkships studied the videos about patient safety and filled out questions associated with patient safety. The average score of the learning outcomes of the patient safety videos was 84.64. The scores ranged from 60 to 100, and the median was 86.66. The answers with the lowest scores were questions about patient safety goals and the accuracy of patient identification. The aspects of knowledge about drug allergy, hand hygiene, reduction in inpatient fall, and identification of blood transfusions were answered correctly by all participants. The outcomes of the clinical clerkship learning are still varied. Further research is required to compare learning outcomes before and after studying educational videos with a broader domain.Abstrak: Keselamatan pasien merupakan hal utama yang harus diperhatikan dan digalakkan dalam setiap pelayanan kesehatan di berbagai tingkat fasilitas kesehatan. Hal ini sangat menonjol bagi mahasiswa, terutama kepaniteraan klinis, sebagai calon dokter. Saat ini penggunaan video pendidikan merupakan media pembelajaran yang populer bagi siswa. Namun, tidak ada penelitian yang mengungkapkan bagaimana kepaniteraan klinis terpapar pada keselamatan pasien setelah belajar melalui video sebelum mengikuti pendidikan di rumah sakit pendidikan. Penelitian ini bertujuan untuk mendeskripsikan hasil pembelajaran video edukasi keselamatan pasien di kepaniteraan klinik. Penelitian ini menggunakan metode deskriptif-analitik. Dua puluh tiga kepaniteraan klinis mempelajari video tentang keselamatan pasien dan mengisi pertanyaan yang terkait dengan keselamatan pasien. Rata-rata skor hasil belajar video keselamatan pasien adalah 84,64. Skor berkisar dari 60 hingga 100, dan median adalah 86,66. Jawaban dengan skor terendah adalah pertanyaan tentang tujuan keselamatan pasien dan ketepatan identifikasi pasien. Aspek pengetahuan tentang alergi obat, kebersihan tangan, pengurangan pasien jatuh rawat inap, dan identifikasi transfusi darah dijawab dengan benar oleh seluruh partisipan. Hasil pembelajaran kepaniteraan klinik masih bervariasi. Diperlukan penelitian lebih lanjut untuk membandingkan hasil belajar sebelum dan sesudah mempelajari video pendidikan dengan domain yang lebih luas.